Design and hardware implementation of conditioning circuit for accurate reading from transducers with nonlinear responses - Hasan, Khairul; Md Ralib, Aliza Aini Binti; Arshad, Maliya Atika; Khan, Sheroz (IIUM Press, 2011)

(untitled)
This chapter is about design and hardware implementation of a signal conditioning circuit that has the ability to read the output response of a non-linear sensor and produce corresponding linear results. This design is based on piecewise linearization technique. First the non-linear output of the sensor's curve divided into the linear segment each segment is identified by its corresponding slope. A couple of comparators has used for selecting the individual line segment (voltage range) and then by the help of instrumentation amplifier circuit the input voltage interpret into desired output voltage. The simulation of the whole circuit is done in order to make everything easy to understand and visible.